Energy complexity of optical computations - Tyagi, A.; Reif, J. (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
The paper provides lower bounds on the energy consumption and demonstrates an energy-time trade-off in optical computations. All the lower bounds are shown to have the matching upper bounds for a transitive function-shifting. Since the energy consumption in an optical transmission is a nonlinear function of the distance, a new setof techniques was required to derive these lower bounds. It also characterizes the energy requirements of 3-D VLSI computations.< >